Notorious: Hitchcock’s good neighbor film Notorious: Hitchcock’s good neighbor film - Arlindo Castro (Ilha do Desterro, 2008)
The New York release of Alfred Hitchcock’s Notorious occurred
in August 1946, one month after the Bikini atomic explosions, and one year after the bombing of Hiroshima and Nagasaki. “Is mankind dying of curiosity?” asked a double page Time magazine ad, in the same issue that published a review of the film. “Time’s Science department noted recently,” readers were told, “that people everywhere have one great Fear: will the curiosity of nuclear physicists someday set off a giant chain reaction which will flash-bum the world to a clinker?”l To overcome that fear of the nuclear apocalypse, according to the add, readers should learn more and more about “the big mysteries of our atomic age,” beginning by checking her or his score in the “Time’s
Quiz on Science.” If they happened to go to Radio City Music Hall, Notorious would reassure them that the U.S. was doing well in preventing obstinate Nazis from making an atomic bomb, though at that moment of the nuclear espionage war, former Manhattan Project insider Klaus Fuchs had actually passed on to a Soviet contact in London classified information about the Manhattan Project and American atomic plans.2 Indeed, in that transitional period between World War II and
the Cold War, the major political villains were still Nazis, not
Communists, as exemplified by other 1946 films like Orson Welles’ The Stranger, Charles Vidor’s Gilda, and Edward Dmytryk’s Cornered. The New York release of Alfred Hitchcock’s Notorious occurred
in August 1946, one month after the Bikini atomic explosions, and one year after the bombing of Hiroshima and Nagasaki. “Is mankind dying of curiosity?” asked a double page Time magazine ad, in the same issue that published a review of the film. “Time’s Science department noted recently,” readers were told, “that people everywhere have one great Fear: will the curiosity of nuclear physicists someday set off a giant chain reaction which will flash-bum the world to a clinker?”l To overcome that fear of the nuclear apocalypse, according to the add, readers should learn more and more about “the big mysteries of our atomic age,” beginning by checking her or his score in the “Time’s
Quiz on Science.” If they happened to go to Radio City Music Hall, Notorious would reassure them that the U.S. was doing well in preventing obstinate Nazis from making an atomic bomb, though at that moment of the nuclear espionage war, former Manhattan Project insider Klaus Fuchs had actually passed on to a Soviet contact in London classified information about the Manhattan Project and American atomic plans.2 Indeed, in that transitional period between World War II and
the Cold War, the major political villains were still Nazis, not
Communists, as exemplified by other 1946 films like Orson Welles’ The Stranger, Charles Vidor’s Gilda, and Edward Dmytryk’s Cornered.